Design and Implementation of Cuk H-Bridge Inverter Voltage Control using STM32F407VET6 - ANGGORO, GIOVANI CHRISANTUS; PRATOMO, LEONARDUS HERU (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2025)
The development of renewable energy utilizing electrical power conversion devices is growing rapidly. Electrical power conversion in an inverter works by converting DC into AC. Typically, the inverter works as a voltage reducer, but under certain conditions, it works as a voltage booster with a limited operating range. To overcome the problems, an inverter with a voltage-increasing and decreasing converter is implemented in the same circuit. This research has investigated the combination of an inverter with a Cuk Converter so that it becomes a Cuk H-Bridge Inverter with voltage boosting and reducing control. The Cuk H-Bridege Inverter implements eight power switches by combining the H-Bridge Inverter and Cuk Converter. LV25-P voltage sensor detects constant output voltage with integral proportional control using STM32F407VET6 microcontroller. The laboratory uses equipment according to the standard. A Total Harmonic Distortion (THD) generated in the test meets the IEEE 519 standard of 4.1%.